Nutritional, chemical, and antioxidant evaluation of different Armuña lentil cultivars (Len culinaris spp): Influence of soil composition and year - Liberal, Ângela (2022)
Lentis (Lens culinaris Medik) are a fast-cooking legume widely consumed around the world due to their valuable nutritional and chemical profiles.